Natural Resources and Revenue Sharing in the New Federal System of Nepal: A Proposed Model - Pandit, Bishnu H; Shrestha, Him L (The Initiation, 2010)
This article considers recent trends in federalism, with particular attention to revenue sharing of natural resources in the new federal system of Nepal. It begins with a general description of the federal system prevailing in other countries, revenue sharing pattern and possible ways that can be implemented in Nepal. The article concludes with an explanation of trends that set the direction for policy innovations in natural resources federalism and general thoughts about the future of federalism in natural resources law in Nepal, which in turn can be reflected in the new constitution. A model consisting of seven provinces based on five criteria (river and hydro-power; forest, wild life and national parks; population/ethnicity; geographic location; and road networks) is also proposed for restructuring new Nepal. Three levels (center, province and local/or community) of new Nepal federal system are proposed. Recommendations are made to be included in the fundamental right and state responsibility part of the constitution. Key words: Fedral system, Economic right, Constitution, Revenue sharing, Natural resources management DOI: 10.3126/init.v3i0.2426 The Initiation Vol.3 2009 p.38-48